Integrated ABC–VED–AHP Framework for Prioritizing Returned Materials in Electricity Transmission Warehouse Management - Muhammad Dias Rizal Adianto; Niniet Indah Arvitrida (Jurnal Teknologi dan Manajemen Industri Terapan, 2026)
Returned materials in electricity transmission warehouses may still possess economic value and operational utility, but their accumulation reduces warehouse efficiency and delays asset recovery decisions. This study aims to develop an integrated decision framework for prioritizing returned materials. The proposed framework combines ABC analysis, VED analysis, physical condition assessment, reuse potential evaluation, and the Analytic Hierarchy Process (AHP), and was applied to 580 returned material items with a total replacement value of IDR 256,057,003,073. The results show that operational criticality is the most influential criterion (0.5342), followed by physical condition, economic value, and reuse potential. The consistency ratio (0.0455) indicates reliable expert judgment. The final prioritization classified 397 items as High Priority, 116 as Medium Priority, and 67 as Low Priority. The proposed framework provides an objective and data-driven approach for returned material management, supporting warehouse optimization, dead stock reduction, and improved asset recovery in electricity infrastructure systems.